Nicholas St. North and the battle of the Nightmare King - Joyce, William, 1957- (Joyce, William, 1957- Guardians, 2011)
Nicholas St. North, a daredevil swordsman seeking treasure in the fiercely guarded village of Santoff Claussen finds, instead, the great wizard Ombric Shalazar and a battle against the Nightmare King and his evil Fearlings--a battle Nicholas can win only if he finds five other Guardians in time.